Karakteristik Berat Bayi Lahir Rendah di RSUD Tabanan - I Komang Galih Vedanta Artana; Dewa Ayu Putri Sri Masyeni; Putu Arya Suryanditha (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
According to WHO, LBW is the condition of a baby with a birth weight of less than 2500 grams. LBW can occur due to maternal age, education, lack of nutritional intake, gap of pregnancy, parity, socioeconomic factors, fetal factors, and the placenta. This study aimed to determine the characteristics of LBW babies, maternal risk factors, and the average LBW in Tabanan Regional Hospital, Bali Province. A descriptive observational design with a cross-sectional approach on Tabanan Hospital medical record data 2020-2022 was used in this study. The sample was determined using consecutive sampling and 116 samples were acquired. The results showed that 87.9% of LBW babies were in the low category and 62.1% were male, most babies were born to mothers who were not at risk, 78.4% were from mothers aged 20-35 years, 65.5% were from mothers with multiparous parity, 78.4% were born at term pregnancy age, 77.6% were born with pregnancy gaps > 2 years, and 89.7% came from families without a history of LBW. Some babies were born to mothers with pregnancy complications, such as preeclampsia (15.5%), gestational hypertension (31.9%), anemia (28.4%), and premature rupture of membranes (24.1%). Some mothers had disease’s history. such as diabetes (9.5%), asthma (7.8%), hypertension (18.1%), HIV (2.6%), and syphilis (0.9%).